A mini review of healthy bars – purchasing motives and challenges: towards Halalan Toyyiban approach - Mohd Noor, Nurul Auni; Hazahari, Noor Yuslida; Shahidan, Norshazila (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2022)
Nowadays, the consumption of healthy bars has increased worldwide due to the nutritional values and versatility of the products. The latest study explains these different healthy bars, their typical ingredients, and consumers’ growing awareness on food safety and quality simultaneously demanding halal-certified products. This review article compares different healthy bars that influence consumers’ purchasing motives and elaborates on the obstacles producers encounter while producing these healthy bars using halal and toyyib. The review was carried out by going through information from 98 publications related to four types of nutritious bars: (i) cereal-based bars, (ii) energy bars, (iii) fruit-based bars and (iv) vegetable-based bars. Meanwhile, the packaging attribute is the most crucial component influencing consumers’ purchasing decisions. Manufacturers discovered the most challenging tasks are keeping up with the demand for unique ingredients in healthy bars and not forgetting consumers’ demand for halalan toyyiban food products.